Optical feedback cooling of a mechanical silicon oscillator with a single laser - Nätkinniemi, Joonas (2020)
Optical feedback cooling was attempted on a split silicon beam photonic crystal oscillator, which acts as an optical cavity and a micromechanical resonator. The cooling setup uses a single laser for the dual roles of position measurement and feedback via amplitude modulation. The theoretical basis of optomechanical feedback cooling is explored, and expected spectrum of the feedback experiment is simulated. Feedback experiments were performed and the resulting spectrums were plotted and analyzed. Because of mistakes made in the experiment setup, significant unwanted parasitic feedback effect was encountered during the feedback experiments, which resulted in no detectable cooling effect. The probable significant causes of the parasitic feedback were identified and ways to correct them proposed for possible follow up experiments.